The impact of voice blogging on the oral proficiency of upper secondary students in l2 kazakh speaking (Journal of Educational Sciences, 2024)
This study had the goal to assess the impact of a 12-week voice blogging intervention on the oral proficiency of Russian-speaking upper secondary students learning Kazakh in Kazakhstan. A total of 84 learners were randomly assigned to either an experimental group, which engaged in weekly voice recording and posting via WhatsApp outside of regular class time, or a control group that received standard classroom instruction without any extracurricular speaking in Kazakh. The speaking output of both groups was evaluated based on complexity, fluency, and accuracy measures before and after the intervention. Additionally, the experimental group completed a questionnaire after the experiment to provide insights into their perceptions of the course. The results revealed that learners in the trial group exhibited significantly higher levels of complexity and fluency in their post-test narrations as opposed to the no-blogging group. However, there was no significant effect on speech accuracy. The schoolers' feedback on the audio blogging activity was positive. These findings suggest that audio blogging can be an effective and engaging method to hone L2 speaking skills.Keywords: L2 speaking, Kazakh language, oral performance, audio blogging, second language.